2018
DOI: 10.1136/bmjsrh-2018-200095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a case management programme for women seeking later second-trimester abortion: the case of the Massachusetts Access Program

Abstract: The Access Program, through its referral and case management network, was a valuable resource both to patients seeking later second-trimester abortions and providers involved in abortion care. It acts as one example of an effective, highly acceptable and potentially replicable intervention to reduce barriers to obtaining later second-trimester abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Inspired by the demonstrated efficacy of care navigation support in improving outcomes for gynecologic cancer, McKenney, Martinez, and Lee (2018) have identified the potential of care navigators to enhance access to care and promote selfefficacy for individuals seeking pregnancy termination. The Massachusetts Access Program, an abortion care navigation program for individuals with complex medical and social needs, has operated for more than a decade, providing information to up to 500 individuals and intensive case management to approximately 200 individuals seeking abortion annually (Ho & Janiak, 2018). A recent evaluation found the Access Program highly acceptable to abortion care providers, who report their patients benefit from the logistical assistance and patient education that the navigator provides (Ho & Janiak, 2018).…”
mentioning
confidence: 99%
“…Inspired by the demonstrated efficacy of care navigation support in improving outcomes for gynecologic cancer, McKenney, Martinez, and Lee (2018) have identified the potential of care navigators to enhance access to care and promote selfefficacy for individuals seeking pregnancy termination. The Massachusetts Access Program, an abortion care navigation program for individuals with complex medical and social needs, has operated for more than a decade, providing information to up to 500 individuals and intensive case management to approximately 200 individuals seeking abortion annually (Ho & Janiak, 2018). A recent evaluation found the Access Program highly acceptable to abortion care providers, who report their patients benefit from the logistical assistance and patient education that the navigator provides (Ho & Janiak, 2018).…”
mentioning
confidence: 99%
“…Somewhat paradoxically, participants in our study also reported medical professionals to be a key source of information about abortion services [ 46 ]. As such, the medical system may act both to delay access to care for some, and as a valuable source of information for others [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NYC Health + Hospitals created a new position of “Client Navigator,” following a successful model that was created in Massachusetts. 17 The Client Navigator’s primary role will be to accompany patients who need logistic or financial support through their abortion care experience, linking them to necessary resources and ensuring timely access to care. The Client Navigator will also support health care professionals both inside and outside the public health care system who are seeking referrals for their patients.…”
Section: Accessibilitymentioning
confidence: 99%